If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(1 + 7x) + -6(7 + -7 + -1x) = 36 (1 * -1 + 7x * -1) + -6(7 + -7 + -1x) = 36 (-1 + -7x) + -6(7 + -7 + -1x) = 36 Combine like terms: 7 + -7 = 0 -1 + -7x + -6(0 + -1x) = 36 -1 + -7x + -6(-1x) = 36 Remove parenthesis around (-1x) -1 + -7x + -6 * -1x = 36 Multiply -6 * -1 -1 + -7x + 6x = 36 Combine like terms: -7x + 6x = -1x -1 + -1x = 36 Solving -1 + -1x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 36 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 36 + 1 -1x = 36 + 1 Combine like terms: 36 + 1 = 37 -1x = 37 Divide each side by '-1'. x = -37 Simplifying x = -37
| x/2+3=13 | | 13/2+3=x | | 15+16=x | | x^2-15x+40=-10 | | (-2)(-1/10) | | M^2+4m=m+18 | | (17/20)(-3/2) | | Y^3+2y^2=8y | | 1/4-x=(-3/8) | | 0=-16t^2+50t+10 | | y=3x+Kx-1 | | 2x^1/2-9x^1/4+6=0 | | 3x-(x+5)/2=x+8 | | -186=2-4(7n-2) | | 2(30)+24=180 | | 2(30)+24=60 | | (-20)(1/4) | | 3(5-4x-3+3x)=2x(4x-3-3x-3) | | 2p^2+11p+14=0 | | 3x-x+5/2=x+8 | | 3/-5+(1/-5) | | -112=-4+4(1+7v) | | -3/8+(-5/8) | | 4n+5-3=-10 | | 2(30)+24=30 | | (-1)(-12/13) | | s(t)=-16t^2+76t+46 | | 1/3-x=-1/2 | | 3(6-x)=23 | | (5x+7)-(7x^2+3x+9)= | | 2(r+5)=16 | | (a-26)(a+144)=0 |